CONSUMER PROTECTION IN AN UNJUST ECONOMIC SYSTEM: A CRITIQUE OF THE WEAKNESSES IN CONSUMER PROTECTION LAW, HUMAN RIGHTS, AND PUBLIC POLICY - Zulkifli; Sofyan Jafar; Muhibuddin; Teuku Yudi Afrizal; Nasrianti (PT. Radja Intercontinental Publishing, 2025)
The rapid development of the digital economy in Indonesia, with a transaction value of IDR 487.01 trillion in 2024, has expanded access to goods and services, but it has also exacerbated significant injustices faced by consumers. As digital platforms become more dominant, consumers are increasingly vulnerable to issues such as misleading product information, data misuse, unfair business practices, and imbalanced bargaining power between businesses and consumers. This study aims to analyze consumer protection within an unjust economic system, from the perspectives of consumer protection law, human rights, and public policy. Using a normative juridical methodology with statutory, conceptual, and comparative approaches, this study finds that Indonesia's Consumer Protection Law (Law No. 8 of 1999) remains largely focused on formal ownership protection, yet fails to effectively address the complexities of digital transactions and information asymmetries in the digital economy. From the perspective of human rights, consumer protection emphasizes fairness, the prohibition of deception, and the protection of public interest. Meanwhile, human rights principles affirm the consumer's right to safety, accurate information, and economic justice. The study argues that public policy needs to be reconstructed to strengthen the state's responsibility, improve business accountability, ensure transparency in product information, guarantee ethical products, and establish more effective dispute resolution mechanisms. Thus, consumer protection in the digital economy must go beyond legal certainty and focus on distributive justice and the fulfillment of human rights in the digital realm.